2017
DOI: 10.1021/acs.jpcc.7b07112
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adhesion at the Alumina/Zinc Interface by Stainless Steel Buffers

Abstract: The weak interaction between zinc and alumina is responsible for a poor performance of anti-corrosive galvanic zinc coatings on modern advanced high strength steels. In this context, we report a theoretical study on the eect of realistic multi-component metal buers on the adhesion strength of a model-alumina(0001)jzinc interface. Relying on results of ab initio calculations on relevant individual oxidejoxide, oxidejmetal, and metaljmetal interfaces (separation and interface energies), we determine by Monte Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…Before concluding, let us note that the overall pattern of zinc interaction at various terminations of silica shows clear similarities with zinc interaction at the α-alumina(0001) surfaces 44 . This suggests that, similarly to the case of alumina, adhesion improvement of zinc/silica interfaces may require the presence of interfacial buffers made of more reactive elements [45][46][47] . However, we stress that surface siloxane rings, which are a structural peculiarity of the non-polar silica surfaces, may require specific treatment to break them.…”
Section: Discussionmentioning
confidence: 99%
“…Before concluding, let us note that the overall pattern of zinc interaction at various terminations of silica shows clear similarities with zinc interaction at the α-alumina(0001) surfaces 44 . This suggests that, similarly to the case of alumina, adhesion improvement of zinc/silica interfaces may require the presence of interfacial buffers made of more reactive elements [45][46][47] . However, we stress that surface siloxane rings, which are a structural peculiarity of the non-polar silica surfaces, may require specific treatment to break them.…”
Section: Discussionmentioning
confidence: 99%
“…, and E (Au) are the total energies of the oxide-covered slab, a freestanding fully relaxed oxide layer, and the bare gold slab, respectively. The calculated adhesion energy is 2.34 J/m 2 (4.2 eV per Nb 2 O 3 formula unit or 14.6 eV/nm 2 ), typical of strongly interacting metal/oxide interfaces or other honeycomb transition metal oxides on Au(111) [24,40]. This number can be decomposed into two contributions, namely the elastic energy necessary to constrain the lattice parameter of the freestanding honeycomb monolayer to that of the gold substrate (−1.8 eV) and the oxide-metal interaction energy gained when bringing the constrained oxide film into contact with the Au(111) surface (6.0 eV).…”
Section: B Adhesion Energymentioning
confidence: 98%
“…One alternative path may rely on using interfacial buffers composed of more reactive metals. Indeed, in the superficially similar case of alumina/zinc interfaces, we have previously shown that early transition metal 38 or stainless steel 39 buffers can significantly enhance adhesion resulting in cohesive cleavage within the zinc deposit. However, the similarity between the two systems is limited.…”
Section: Introductionmentioning
confidence: 99%